Implementing a RtI tier 2 mathematics lab in a middle school. Issue 3 (3rd July 2019) - Bouck, Emily C.; Park, Jiyoon; Bouck, Mary K.; Sprick, Jessica; Buckland, Angela
Abstract: Response to intervention (RtI) in secondary schools is a viable option for mathematics, but limited research exists. In the study, students who received just Tier 1 (i.e., general education mathematics class) and students who received both Tier 1 and Tier 2 (i.e., a math lab) completed a pretest and posttest of grade-level content. The results suggest no statistically significant difference between the overall mean assessment gain scores of the two groups. The Tier 2 math lab intervention as implemented did not further exacerbate mathematical differences between struggling students and their peers but it did not work to decrease the mathematics deficits of students needing intervention either. The efficacy of a Tier 2 math lab as a RtI system at the secondary level can be questioned.